Excess body weight and its associated factors among first-year health sciences university students in Indonesia. - Dhanasari Vidiawati; Retno Asti Werdhani; Junaiti Sahar; Fitriana Murriya Ekawati; Linda Dewanti; Pudji Lestari; Endang R Surjaningrum; Sulistiawati Sulistiawati; Indah Suci Widyahening (PLoS ONE)
The incidence of overweight/obesity has been increasing among adolescents and young adults worldwide. University graduates majoring in health sciences are expected to become role models and agents of change in the future. Hence, the aim of this study was to understand the prevalence of excess body weight and risk factors among the university students in health sciences from the three biggest universities in Indonesia when they first entered the university. This cross-sectional study recruited all first-year students using a self-administered questionnaire and physical and laboratory examination data in 2022. The outcome was the prevalence of excess body weight, and the associated factors were students' demographic characteristics, eating habits, and physical activities. Associated factors were measured by computing the odds ratio using logistic regression analysis. A total of 1,552 first-year students were included in the final analysis, and 77.6% were women. The prevalence of excess body weight was 34.7%. Independent factors, which increased the risk of excess body weight, were being male (adjusted odds ratio [AOR], 2.58; 95% CI 1.99-3.35), having a family history of obesity (AOR, 2.91; 95% CI 2.09-4.06), and eating <3 meals/day (AOR, 1.40; 95% CI 1.10-1.80). The prevalence of excess body weight among first-year health sciences university students in Indonesia was high. The health sciences faculties should design a curriculum which not only ensures that the students can provide health care to the communities in the future but also apply the knowledge to improve their health.